2008
DOI: 10.1016/j.bcmd.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional platelet abnormalities in Berkeley sickle cell mice

Abstract: Berkeley sickle cell mice are used as an animal model of human sickle cell disease but there are no reports of platelet studies in this model. Since humans with sickle cell disease have platelet abnormalities, we studied platelet morphology and function in Berkeley mice (SS). We observed elevated mean platelet forward angle light scatter (FSC) values (an indirect measure of platelet volume) in SS compared to wild type (WT) (37 ± 3.2 vs. 27 ± 1.4, mean ± SD; p <0.001), in association with moderate thrombocytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 93 publications
2
13
0
Order By: Relevance
“…[7][8][9][10][11] Murine models of SCD offer the potential to better understand the pathophysiology of SCD and to identify novel therapeutic targets. 42 Studies using a variety of SCD models have revealed increased adhesive interactions between circulating erythrocytes and leukocytes with the endothelium, which can impede microvascular perfusion and promote vasoocclusive events. 1 However, it is important to recognize the limitations of the currently available SCD models, because none of them truly mimics human disease (mainly because of the complexities of SCD and the apparent contribution of multiple biologic processes to the vasculopathy associated with this disease).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Murine models of SCD offer the potential to better understand the pathophysiology of SCD and to identify novel therapeutic targets. 42 Studies using a variety of SCD models have revealed increased adhesive interactions between circulating erythrocytes and leukocytes with the endothelium, which can impede microvascular perfusion and promote vasoocclusive events. 1 However, it is important to recognize the limitations of the currently available SCD models, because none of them truly mimics human disease (mainly because of the complexities of SCD and the apparent contribution of multiple biologic processes to the vasculopathy associated with this disease).…”
Section: Discussionmentioning
confidence: 99%
“…18 When thrombocytopenia was detected in a sample, it was confirmed using flow cytometry with a fluorescently labeled mAb to mouse GPIb␤ as previously described. 18 Preparation of mouse platelet lysate, platelet releasate, serum, and plasma…”
Section: Hematologic Datamentioning
confidence: 99%
“…Whole blood platelet count was determined with an automated instrument (ADVIA120) and by flow cytometry using a fluorescently labeled mAb to mouse GPIb␤. 18 Plasma samples were prepared by immediately centrifuging the samples at 12 000g for 5 minutes at RT. No platelet contamination was observed in the plasma prepared by this method.…”
Section: Induction Of Thrombocytopenia In Micementioning
confidence: 99%
“…15,16 Thrombocytosis and platelet activation are also well-recognized features of SCD. 4,13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Thrombotic events including pulmonary embolism, deep vein thrombosis, and SCD-related stroke are common. 17,[36][37][38][39][40] SCD-associated pulmonary hypertension (PHT) is associated with endothelial cell activation (as measured by soluble vascular cell adhesion molecule-1 [sVCAM-1]), which would also support procoagulant activity.…”
Section: Introductionmentioning
confidence: 99%